2016
DOI: 10.1007/s11207-016-0940-z
|View full text |Cite
|
Sign up to set email alerts
|

Using SDO/HMI Magnetograms as a Source of the Solar Mean Magnetic Field Data

Abstract: The solar mean magnetic field (SMMF) provided by the Wilcox Solar Observatory (WSO) is compared with the SMMF acquired by the Helioseismic and Magnetic Imager (HMI) onboard the Solar Dynamic Observatory (SDO). We found that despite the different spectral lines and measurement techniques used in both instruments the Pearson correlation coefficient between these two datasets equals 0.86 while the conversion factor is very close to unity: B(HMI) = 0.99(2)B(WSO). We also discuss artifacts of the SDO/HMI magnetic f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 27 publications
2
6
0
Order By: Relevance
“…Plots of the SMMF and the weighted MMFs corresponding to the different features (as in Equation (3)) on the solar surface are shown in Figure 3 as a function of time, for the entire analysis period. Figure 3(A) shows the peak value of the SMMF to be about 2.5 G that occurred in 2014 December and is consistent with Kutsenko & Abramenko (2016). The dotted vertical line corresponds to 2014 April, which corresponds to the maximum of solar cycle 24.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…Plots of the SMMF and the weighted MMFs corresponding to the different features (as in Equation (3)) on the solar surface are shown in Figure 3 as a function of time, for the entire analysis period. Figure 3(A) shows the peak value of the SMMF to be about 2.5 G that occurred in 2014 December and is consistent with Kutsenko & Abramenko (2016). The dotted vertical line corresponds to 2014 April, which corresponds to the maximum of solar cycle 24.…”
Section: Resultssupporting
confidence: 72%
“…These measurements are generally made by letting unfocused light pass through a spectrograph slit (making sure that light from all parts of Sun is integrated) followed by measuring Zeeman splitting of the spectral lines under consideration using a Babcock-type magnetograph. Boberg et al (2002), and more recently Kutsenko & Abramenko (2016), have shown that the SMMF can also be calculated by averaging the full-disk LOS magnetograms provided by the space-based Michelson Doppler Imager (Scherrer et al 1995) on board the Solar and Heliospheric Observatory and the Helioseismic and Magnetic Imager (HMI; Schou et al 2012) on board the Solar Dynamics Observatory, (SDO; Liu et al 2012;Scherrer et al 2012), respectively. This has significantly improved the chances of obtaining such measurements continuously more or less uninterrupted, which otherwise is limited by lack of continuous availability of clear skies in ground-based observations.…”
Section: Introductionmentioning
confidence: 99%
“…03.2011 & 30.11.2017 The right panel of figure 1-(A), shows the temporal variation of the SMMF. It is found to have a peak value of about 2.5 G that is consistent with Kutsenko et al (2016). The mean background field ( figure 1-(B)) emulates the SMMF quite distinctly, both peaking around December 2014.…”
Section: Contribution Of Various Surface Magnetic Features To the Obssupporting
confidence: 66%
“…Smirnova et al (2013b,a) found that the amplitude of these oscillations increases rapidly when the field strength exceeds 2000 G in the magnetic fields of ARs. Kutsenko & Abramenko (2016) further argued for the presence of these two artificial oscillations by studying wavelet transform of the solar mean magnetic field measurements. If these oscillations were indeed significant in the helicity components presented in this work, we would expect to see them in the WPS of all ARs, particularly in the non-flaring regions where there are very few periodicities of significant power.…”
Section: Discussionmentioning
confidence: 99%